KETELADANAN TOKOH PEMBEBAS BAITUL MAQDIS : Analisis Riwayat Mengenai Yusya Bin Nun - Hakim, Ridwan; Renaldi, Haris (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2022)
Baitul Maqdis has a very long history and has even alternated the power of Tauhid and the power of tyrants ruling there. At a time when Muslims were required to fight back so that Tauhid and justice would be established there by expelling the colonialism, the Muslims should reread the history of the heroes of the liberation of Baitul Maqdis. Among the heroes of Tauhid who have ever existed is Yusya bin Nun. This study aims to explore the narrations in the story of Yusya bin Nun using the tahlili method (descriptive analysis). The author will explain these narrations by describing the aspects and meanings contained in them and then conclude and explain the aspects of exemplary for the generation of Baitul Maqdis struggle. The results of this study indicate that there are at least three narrations used to narrate the history of Yusya bin Nun, and there are five aspects of exemplary that are concluded, namely; first, the mental attitude of reverence and sacrifice in studying which is illustrated in the history of Musa's meeting with Khidr; second, loyalty as a soldier based on piety, as illustrated in the history of the events of the Bani Israel's refusal to enter Baitul Maqdis; third, fighting the attitude and mental of